It shouldn't be this hard: Systemic, situational, and intrapersonal barriers to exiting homelessness among homeless young adults. (July 2020) - Sample, Katie; Ferguson, Kristin M
The purpose of this qualitative study was to explore homeless young adults' perceptions of the systemic, situational, and intrapersonal barriers they encounter across multiple systems in trying to exit homelessness and the ways these barriers are interrelated. Thirty-one homeless young adults (ages 18–26) in Phoenix and Tempe, Arizona were recruited for in-depth interviews from two resource centers serving homeless youth. Template analysis was used to systematically analyze and code participants' verbatim transcripts from the interviews into a template (codebook). Characteristic quotes from the interviews are used to illustrate the emergent themes. Findings indicate that structural barriers faced by homeless youth include inadequate homeless resources, employment challenges, discrimination by law enforcement, hot climate, lack of transportation, and legal concerns. Situational barriers include interpersonal relationships, the street environment, and lack of personal resources. Intrapersonal barriers include behavioral, mental, and physical health challenges, reluctance to reach out for help, money management, and lack of desire for stable housing. Participants also outlined multiple ways in which these barriers interact to hinder their exiting homelessness. Findings support current literature applying ecological theory to the issue of homelessness while highlighting young people's own contextual descriptions of their lived experiences. Three approaches are recommended for improving homeless services with integrated housing, employment, and clinical interventions to help young adults successfully exit homeless.